Recent advances in the synthesis of oxaspirolactones and their application in the total synthesis of related natural products - Thorat, Sagar S (Organic & Biomolecular Chemistry, 2019)
Oxaspirolactones are ubiquitous structural motifs found in natural products and synthetic molecules with a diverse biochemical and physicochemical profile, and represent a valuable target in natural product chemistry and medicinal chemistry. Since the 1970s, numerous innovative synthetic methodologies have been reported for these scaffolds in the context of expanding the range of potential building blocks, catalysts, and modes of transformations (racemic or asymmetric protocols). This review focuses on a broad spectrum of approaches toward the synthesis of oxaspirolactones and their potential application in the total synthesis of biologically relevant natural products starting from the first disclosure to the latest report.

Ready access to benzannulated [5,5]-oxaspirolactones using Au(III)-catalyzed cascade cyclizations - Mankad, Yash; Thorat, Sagar S.; Das, Pronay; Krishna, Gamidi Rama; Kontham, Ravindar; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2022)
This work showcases an unprecedented Au(III)-catalyzed cascade cyclization of 2-(4-hydroxyalkynyl)benzoates to access benzannulated [5,5]-oxaspirolactones related to biologically active natural products. This reaction proceeds through an initial 5-endo-dig mode of hydroalkoxylation of the alkynol segment to give the oxocarbenium species (via cyclic enol-ether) followed by the addition of carboxylate onto the oxocarbenium that delivers the oxaspirolactone scaffold. While testing this method's scope, we found that the steric and electronic environment of the hydroxyl group could alter the reaction pathway that delivers isochromenone through a competitive 6-endo-dig mode of attack of the carboxylate onto the tethered alkyne.

Regioselective synthesis of benzannulated [5,6]-oxaspirolactones via Cu(II)-catalyzed cycloisomerization of 2-(5-Hydroxyalkynyl)benzoates - Thorat, Sagar S.; Shimpi, Sagar P.; Sambherao, Pooja I.; Krishna, Gamidi Rama; Kontham, Ravindar (Journal of Organic Chemistry, 2023)
Spiroketals and oxaspirolactones are widely found in biologically active natural products, serving as important structural motifs. In this study, we present a Cu-(II)-catalyzed cascade cycloisomerization of 2-(5-hydroxyalkynyl)-benzoates, enabling the regioselective synthesis of benzannulated [5,6]-oxaspirolactones containing an isochromen-1-one moiety. This strategy offers a rapid and efficient approach to access a diverse array of benzannulated [5,6]-oxaspirolactones. The methodology presented here showcases a broad substrate scope, delivering good yields and scalability up to gram scale. The structures of the oxaspirolactones were unequivocally confirmed through single-crystal X-ray analysis and by analogy using H-1 and C-13-H-1 NMR data.
Keywords: Construction; Isocumarins; Strategies

Ready access to [5,6,5]-Trioxa-spiro and fused ketals via ag-catalyzed cascade annulation of 4-pentyn-1-ols and aldehydes - Vinodkumar, Ramavath; Nakate, Ashwini K.; Gamidi, Rama Krishna; Kontham, Ravindar (Organic Letters, 2024)
In this study, we unveil the versatility of 4-pentyn-1-ols as carbonyl surrogates for the unprecedented synthesis of diverse oxygen heterocycles, including [5,6,5]-bis-spiroketals (trioxadispiroketals) and [5,6,5]-furano-spiroketals related to bioactive natural products. These reactions commence with the pi-activation-induced intramolecular hydroalkoxylation of 4-pentyn-1-ols, yielding cyclic enol ethers, which undergo subsequent three-component annulation with aldehydes in a [2+2+1+1] fashion, resulting in the formation of [5,6,5]-bis-spiroketals. Notably, the distinctive steric features of alkynyl alcohols, particularly those with a secondary or tertiary alcohol functionality, dictate divergent reaction pathways, leading to the formation of [5,6,5]-furano-spiroketals.